1983
DOI: 10.1017/s0043174500068612
|View full text |Cite
|
Sign up to set email alerts
|

Response of Soybeans (Glycine max) to Planting in Untilled, Weedy Seedbed on Clay Soil

Abstract: Soybeans [Glycine max(L.) Merr.] were planted in an untilled, stale seedbed and conventionally tilled seedbed of Sharkey clay (Vertic Haplaquept) at Stoneville, Mississippi, in 1979 and 1980 to determine the feasibility of the stale -seedbed approach for soybean production in the Mississippi River Delta. Chemical weed control included applications of preplant, preemergence, and postemergence herbicides. Prickly sida (Sida spinosaL.) was the dominant weed in all tillage and weed-control systems. Perennial speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 11 publications
2
52
1
Order By: Relevance
“…Plots were 4 m (eight NRs or four WRs) wide and 21.5 m (IRR) or 30.5 m (NI) long in both years. All experiments were seeded into a stale seedbed (Heatherly and Elmore, 1983; Heatherly et al, 1993; Heatherly, 1999b) that had been tilled with a disk‐harrow and/or a spring‐tooth field cultivator in the fall. Glyphosate [ N ‐(phosphonomethyl)glycine] at either 560 (1997) or 840 (1998) g a.i.…”
Section: Methodsmentioning
confidence: 99%
“…Plots were 4 m (eight NRs or four WRs) wide and 21.5 m (IRR) or 30.5 m (NI) long in both years. All experiments were seeded into a stale seedbed (Heatherly and Elmore, 1983; Heatherly et al, 1993; Heatherly, 1999b) that had been tilled with a disk‐harrow and/or a spring‐tooth field cultivator in the fall. Glyphosate [ N ‐(phosphonomethyl)glycine] at either 560 (1997) or 840 (1998) g a.i.…”
Section: Methodsmentioning
confidence: 99%
“…Soybean production is greatly influenced by precipitation (Egli and Bruening, 1992). The determination of optimum planting date should take the regional rainfall pattern into consideration, because without optimum water condition, the benefit of early planting time could be negated (Heatherly and Elmore, 1983). Early planting can decrease the risks of water stress during growing season in some regions (Bowers, 1995; De Queiroz et al, 1998); however, sometimes delayed planting is suggested when there is sufficient rainfall (Muchow et al, 1994).…”
Section: Environmental Factorsmentioning
confidence: 99%
“…However, development of soil crusts that increase runoff and impede infiltration is more prevalent with conservation strategies (Dao, 1993; Pikul and Zuzel, 1994). Soil texture can further influence the choice of a suitable tillage system for optimizing yields during stress periods (Cameron and Hermawan, 1993; Heatherly and Elmore, 1983). For example, clayey soils differ from silt loam soils in their infiltration and soil moisture retention capabilities (Sopher and Baird, 1978, p. 62).…”
mentioning
confidence: 99%